Hubungan Dukungan Kader terhadap Pemanfaatan Buku KIA Oleh Ibu Balita di Posyandu Melati 2 - Devi Paulinasari Ameriana; Qomariyah Qomariyah; Desi Soraya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The use of Maternal and Child Health (KIA) books for toddlers at Posyandu Melati 2 in 2023 falls short of the national target of 85%. This low usage rate raises concerns about potential negative impacts on the health of children under five. Cadres play a crucial role in promoting maternal and child health by providing guidance and encouragement regarding the use of KIA books. This study aims to assess the correlation between cadre support and the utilization of KIA books among mothers of toddlers at Posyandu Melati 2 from April to May 2024. A cross- sectional analysis was conducted with a total population of 57 mothers of toddlers, using a total sampling technique. Data on maternal characteristics, cadre support, and KIA book usage were collected through a survey with a questionnaire and analyzed using the chi-square method with a significance level of α = 0.05. Results indicated that only 10.5% of mothers used the KIA books properly, and 28.1% received good support from health workers. The analysis revealed a significant correlation between cadre support and the use of KIA books, with an odds ratio (OR) of 6.5 and a Fisher Exact Test result of p = 0.046. These findings highlight the importance of cadre support in enhancing the use of KIA books among mothers of toddlers, suggesting that increased support could improve usage rates and potentially benefit child health outcomes.